Efektivitas Content Marketing Bagi Peningkatan Omset Usaha Halal Food: Studi pada kripik pisang SANG DEWA - Febri Tri Wilujeng; Ashlihah Ashlihah; Amin Awal Amarudin (Pusat Riset dan Inovasi Nasional, 2024)
In the 5.0 revolution era, entrepreneurs use social media as part of a marketing strategy to increase sales turnover. The level of competition in the snack and souvenir products business is quite high. Other similar businesses have utilized e-marketing strategies in terms of marketing. However, not all social media content created by business actors is effective in increasing their business turnover. The amount of sales turnover is often used as an indicator to assess the development of a business. Sales turnover is the total number of sales of goods or services within a certain period of time, which is calculated based on the amount of money earned. Packaged in simple and attractive packaging and easy to carry anywhere. This research aims to determine the effectiveness of marketing content on halal food business turnover. The method used in this research is a quantitative method. Data collection was carried out by distributing questionnaire questions via Google Form. The results obtained in this research show that there is an influence on the effectiveness of marketing content in increasing the turnover of halal food businesses in the Sang Dewa banana chips business, as shown in the results of the simple linear regression test on the T Test, with a calculated t of 6,506 which is greater than the t table with a value of 1,654. then there is a significant influence of 0.200 > 0.05, therefore the influence of marketing content on increasing the turnover of halal food businesses in Sang Dewa banana chips.